Patients' and health professionals' perspectives regarding shared decision making in the psychiatric inpatient setting - A multiple qualitative case study - Caroline Gurtner; Jos M.G.A. Schols; Christa Lohrmann; Sabine Hahn (Elsevier, 2024)
Objective: Shared decision-making is one promising approach to promoting recovery and person-centred care but seems challenging for implementation in clinical practice. This study aimed to explore how patients and health professionals experience shared decision-making and its facilitators and barriers. Methods: A multiple qualitative case study design was chosen, using a constant comparative method. Multiple data sources were used, including individual interviews, observation, document analysis and a focus group. Results: Through first a within-case analysis and then second a cross-case analysis, four patient profiles and their potential for shared decision-making were constructed. The results indicate that in the daily routine of the psychiatric inpatient setting different forms of decision making are used, even though health professionals advocate shared decision-making as the favored approach. Patients also have varying expectations and perceptions regarding shared decision-making, which is reflected in the degree of their involvement. Conclusion: Shared decision-making could be enhanced in the future by a more proactive communication style and the proactive provision of information on the part of health professionals, in order to enhance patient participation in decision-making. Innovation: The study identified different forms of decision-making within the acute psychiatric inpatient setting, highlighting the gap between the advocated SDM approach and its practical implementation. This divergence is a key aspect, as it underlines the complexity of implementing SDM in real clinical settings.